Fused Filament Fabricated Polypropylene Composite Reinforced by Aligned Glass Fibers - Eugene Shulga (Materials, 2020)
3D printing using fused composite filament fabrication technique (FFF) allows prototyping and manufacturing of durable, lightweight, and customizable parts on demand. Such composites demonstrate significantly improved printability, due to the reduction of shrinkage and warping, alongside the enhancement of strength and rigidity. In this work, we use polypropylene filament reinforced by short glass fibers to demonstrate the effect of fiber orientation on mechanical tensile properties of the 3D printed specimens. The influence of the printed layer thickness and raster angle on final fiber orientations was investigated using X-ray micro-computed tomography. The best ultimate tensile strength of 57.4 MPa and elasticity modulus of 5.5 GPa were obtained with a 90° raster angle, versus 30.4 MPa and 2.5 GPa for samples with a criss-cross 45°, 135° raster angle, with the thinnest printed layer thickness of 0.1 mm.